Eksplorasi Agen Pengendali Hayati Karat Puru Sengon (Uromycladium tepperianum) di Kabupaten Pekalongan - Ananda Putra Septiadi; Wika Gustiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Gall rust recently causes severe damages on sengon (Paraserianthes falcataria [L.] Nielsen) plantation in Doro Subdistrict, Pekalongan Regency, Central Java. The purpose of this research was to explore the potential biological control agens of gall rusts of sengon. Exploration was started with isolation of bark samples contain gall rusts into Potato Dextrode Agar (PDA) medium and sent them to Plant Clinic, IPB. At the same time, the same samples are grown on rice media for an approximately one week incubation period. Samples on PDA would be further investigated by Plant Clinic for determine species names of the biological agents. For efficacy test purpose, 50 gram of sample growth on rice media was mixed with 1 liter water. The suspension was diluted 1: 5, then sprayed on gall rusts symptom directly on sengon in the field. This simple method introduced to local farmer in order to find promising candicates of biological control agents for controlling sengon gall rusts.